Tuberculosis Monitoring Encouragement Adherence Drive (TMEAD): Toward improving the adherence of the patients with drug-sensitive tuberculosis in Nashik, Maharashtra - Saha, Somen; Saxena, Deepak; Raval, Devang; Halkarni, Nishad; Doshi, Rahul; Joshi, Madhav; Sridharan, Mridhula; Sathwara, Jignasa; Yasobant, Sandul; Shah, Harsh; Quazi, Zahiruddin Syed; Rajsekar, Kavitha; et al. (Frontiers in Public Health, 2022)
Introduction: Adherence to TB Medication is one of the critical challenges to Tuberculosis (TB) elimination in India. Digital adherence technologies (DAT) may have the potential to facilitate medication adherence and monitor adherence remotely. Tuberculosis Monitoring Encouragement Adherence Drive (TMEAD) is one of such DAT piloted in Nasik city of Maharashtra from April 2020 to December 2021. The study aims to assess the adherence and cost-effectiveness of TMEAD, compared to the standard of care for drug-sensitive tuberculosis (DSTB) patients residing in the urban areas of Nasik in Maharashtra, India. Methods: A prospective follow-up of new cases of TB as per NTEP residing in the urban geography of the Nasik was done from purposively selected non-contaminating TUs A total of 400 DSTB patients were enrolled, 200 each in the intervention and control arm. Once the patients were enrolled in the Intervention Arm the TMEAD device was provided The study participants were followed for six months longitudinally from the start of their treatment to assess the outcome of treatment. Health-related quality of life (HRQoL) was assessed using the EQ-5D-5L tool at baseline and first follow-up. The total cost and total QALYs gained for the interventions and control were calculated from the decision tree model. Budget impact analysis was done to assess the impact of TMEAD programme in overall state health budget. Results: Overall, 261 patients completed treatment, 108 patients were on treatment, 15 patients died and 16 patients were defaulters over the study period. The study reported overall treatment adherence at 94% among those who completed treatment. Patient reported high levels of treatment adherence in the intervention group (99%) as compared to the Control group (90%). Adherence assessed through analysing trace of Rifampicin in urine sample for intervention arm was 84% compared to control arm (80%). Per beneficiary (discounted) cost for TMEAD was INR 6,573 (USD:83). Incremental cost effectiveness ratio of the intervention is INR 11,599 (USD:146) which shows the intervention is highly cost-effective. Discussion: This study revealed that patient-reported treatment adherence was high in TMEAD as compared to standard therapy of care for the DSTB patients and the intervention is cost-effective.